High Erk activity suppresses expression of the cell cycle inhibitor p27Kip1 in colorectal cancer cells. - Kress, T; Raabe, T; Feller, S (2010)
The molecular heterogeneity of human cancer cells at the level of signaling protein activities remains poorly understood. Using a panel of 64 colorectal (CRC) cancer cell lines the activity status of the MAP kinases Erk1 and Erk2 was investigated. Erk1/2 activity varied greatly within the CRC cell line panel and was not detectably associated with the speed of cell growth in 10 CRC lines analyzed. As expected, mutations in K-Ras or B-Raf were often, albeit not always, linked to high Erk1/2 activity. The phosphorylation of several known Erk1/2 targets investigated did not generally reflect Erk1/2 activity in the 10 CRC lines analyzed. However, the reduction of Erk1/2 activity with MEK inhibitors generally abolished cell growth but only led to an increase of cellular p27Kip1 levels in CRC cells with high Erk1/2 activity levels. The results indicate that high Erk1/2 activation is utilized by some CRC lines to override the cell cycle brake p27Kip1, while others presumably rely on different mechanisms in order to inactivate this important cell cycle brake. Such detailed knowledge of the molecular diversity of cancer cell signaling mechanisms may eventually help to develop molecularly targeted, patient-specific therapeutic strategies and treatments.